Distinct Functional Contributions by the Conserved Domains of the Malaria Parasite Alveolin IMC1h - Coghlan, Michael P.; Tremp, Annie Z.; Saeed, Sadia; Vaughan, Cara K.; Dessens, Johannes T. (Frontiers in Cellular and Infection Microbiology, 2019)
Invasive, motile life cycle stages (zoites) of apicomplexan parasites possess a cortical membrane skeleton composed of intermediate filaments with roles in zoite morphogenesis, tensile strength and motility. Its building blocks include a family of proteins called alveolins that are characterized by conserved “alveolin” domains composed of tandem repeat sequences. A subset of alveolins possess additional conserved domains that are structurally unrelated and the roles of which remain unclear. In this structure-function analysis we investigated the functional contributions of the “alveolin” vs. “non-alveolin” domains of IMC1h, a protein expressed in the ookinete and sporozoite life cycle stages of malaria parasites and essential for parasite transmission. Using allelic replacement in Plasmodium berghei, we show that the alveolin domain is responsible for targeting IMC1h to the membrane skeleton and, consequently, its deletion from the protein results in loss of function manifested by abnormally-shaped ookinetes and sporozoites with reduced tensile strength, motility and infectivity. Conversely, IMC1h lacking its non-alveolin conserved domain is correctly targeted and can facilitate tensile strength but not motility. Our findings support the concept that the alveolin module contains the properties for filament formation, and show for the first time that tensile strength makes an important contribution to zoite infectivity. The data furthermore provide new insight into the underlying molecular mechanisms of motility, indicating that tensile strength is mechanistically uncoupled from locomotion, and pointing to a role of the non-alveolin domain in the motility-enhancing properties of IMC1h possibly by engaging with the locomotion apparatus.